mRNA technology as one of the promising platforms for the SARS-CoV-2 vaccine development - A. A. Ilyichev; L. A. Orlova; S. V. Sharabrin; L. I. Karpenko (Вавиловский журнал генетики и селекции)
After the genome sequence of SARS-CoV-2 (Severe acute respiratory syndrome-related coronavirus 2) was published and the number of infected people began to increase rapidly, many global companies began to develop a vaccine. Almost all known approaches to vaccine design were applied for this purpose, including inactivated viruses, mRNA and DNA-vaccines, vaccines based on various viral vectors, synthetically generated peptides and recombinant proteins produced in cells of insects and mammals. This review considers one of the promising vaccine platforms based on messenger RNA. Until recent years, mRNA-vaccination was out of practical implementation due to high sensitivity to nuclease degradation and consequent instability of drugs based on mRNA. Latest technological advances significantly mitigated the problems of low immunogenicity, instability, and difficulties in RNA-vaccine delivery. It is worth noting that mRNA-vaccines can efficiently activate both components of the immune system, i. e. T-cell and humoral responses. The essential advantage of mRNA-vaccines includes fast, inexpensive, scalable and uniform production providing a large output of desirable products in vitro. Synthesis and purification processes significantly simplify the process technology of mRNA drugs with injectable purity. Thus, mRNA production via in vitro transcription is more advantageous as compared with DNA-vaccines since it is a chemical process without the use of cells. mRNA techniques make it possible to pass all the phases of vaccine development much faster in comparison with the production of vaccines based on inactivated viruses or recombinant proteins. This property is critically important when designing vaccines against viral pathogens as the main problem of disease control includes a time gap between an epidemic and vaccine development. This paper discusses studies on the development of vaccines against coronaviruses including SARS-CoV-2 with special attention to the mRNA technique.